Solve for y 3=-y/11

Math
3=-y11
Rewrite the equation as -y11=3.
-y11=3
Multiply both sides of the equation by -11.
-11⋅(-y11)=-11⋅3
Simplify both sides of the equation.
Tap for more steps…
Simplify -11⋅(-y11).
Tap for more steps…
Cancel the common factor of 11.
Tap for more steps…
Move the leading negative in -y11 into the numerator.
-11⋅-y11=-11⋅3
Factor 11 out of -11.
11(-1)⋅-y11=-11⋅3
Cancel the common factor.
11⋅-1⋅-y11=-11⋅3
Rewrite the expression.
-1⋅(-y)=-11⋅3
-1⋅(-y)=-11⋅3
Multiply.
Tap for more steps…
Multiply -1 by -1.
1⋅y=-11⋅3
Multiply y by 1.
y=-11⋅3
y=-11⋅3
y=-11⋅3
Multiply -11 by 3.
y=-33
y=-33
Solve for y 3=-y/11

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top